Female melanoma and estrogen receptors expression: an immunohistochemical pilot study. Issue 4 (13th May 2022) - Dika, Emi; Lambertini, Martina; Lauriola, Mattia; Veronesi, Giulia; Ricci, Costantino; Tartari, Federico; Tassone, Daniela; Campione, Elena; Scarfì, Federica
Abstract : Epidemiologic data highlight sex differences in melanoma outcome. A putative role of sex hormones is still under investigation. Very few laboratory investigations have focused on the level of expression of estrogen receptors in melanoma. We evaluated the presence of estrogen receptors alpha (ERα) and beta (ERβ) in melanoma specimens from female patients with a previous history of breast carcinoma (BC). Moreover, another group of female patients undergoing ovarian stimulation (OS) were also compared to two control groups matched for age and melanoma staging. The study was performed at the IRCCS Policlinico di Sant'Orsola Hospital's Melanoma Unit from January 2017 to December 2019. The nuclear and cytoplasmatic immunohistochemical staining was evaluated and scored by the percentage of stained tumour cells: 0 (≤20%), 1 (21–50%) or 2 (≥50%). Twenty-eight specimens were analysed. ERβ nuclear presence was detected in all cases of women with a history of breast cancer. Cytoplasmatic ERβ was clearly expressed with a score of 2 in seven cases. In the respective control group, nuclear and cytoplasmatic ERβ expression was much lower. A cytoplasmatic ERα positivity was also detected in almost all cases. In the second group of women who experienced ovarian stimulation for Assisted Reproductive Technology (ART), a lower abundance of nuclear ERs was detected. Conversely, cytoplasmatic ERβ and α expression ranged widely. Melanoma of women treated with anti-estrogen therapy is generally more prone to express estrogen receptors compared with women of the same age and CM staging but also compared with women in fertile age with and without a history of OS.